2022
DOI: 10.1002/slct.202103984
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Synthesis, Antimicrobial Activities and Molecular Docking of Methoxycarboxylated Chalcone Derived Pyrazoline and Pyrazole Derivatives

Abstract: The synthesis of effective antimicrobial therapeutics has become a challenge due to the occurrence of genetic mutations in microbes that reduced the efficiency of drugs. A new series of heterocyclic chalcone derivatives (1 a‐g, 2 a‐g, 3 a‐g, 4 a‐g) were designed with 52.64‐93.69 % yield under microwave and scrutinized for their antimicrobial activities on Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) via turbidimetric and disc diffusion method. Carboxylated pyrazoline derivatives (3 a‐g) gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Since the chalcone spine is very useful in the preparation of substances with medicinal potential for different diseases [ 25 ] Several chalcone derivative like Isobavachalcone was extracted from Psoralea corylifolia which demonstrated significant antimicrobial effect with MIC of 8 μg/mL on MRSA strains [ 26 ]. Chalcone exhibited significant antimicrobial activity against both Staphylococcus aureus and Escherichia coli [ 27 ]. In 2023, M. Yadav et al synthesized a chalcone derivative which showed MIC of 0.012 mol/mL against P. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%
“…Since the chalcone spine is very useful in the preparation of substances with medicinal potential for different diseases [ 25 ] Several chalcone derivative like Isobavachalcone was extracted from Psoralea corylifolia which demonstrated significant antimicrobial effect with MIC of 8 μg/mL on MRSA strains [ 26 ]. Chalcone exhibited significant antimicrobial activity against both Staphylococcus aureus and Escherichia coli [ 27 ]. In 2023, M. Yadav et al synthesized a chalcone derivative which showed MIC of 0.012 mol/mL against P. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological activities of the pyrazole derivatives are well illustrated by a large number of commercially effective drugs. [11,12,13,14,15] Pyrazole derivatives have also been demonstrated to possess versatile biological activities such as anticancer, [16,17,18] antifungal, [16] antitubercular, [19,20] antiinflammatory, [21,22] antialzheimer's, [23] antimalarial, [24] antimicrobial, [25,26] and antidiabetic [27] … Two notable examples are Celecoxib and Fluconazol (figure 1), which are pyrazolebased compounds being marketed as antimicrobial agents. [28,29] Hydrazide compounds received extensive attention due to their varied biologically effective drugs.…”
Section: Introductionmentioning
confidence: 99%